The Lages diatremes: mineral composition and petrological implications - Barabino,Giancarlo (2007)
Chemical data of heavy minerals from Lages diatremes in southern Brazil have been studied with the aim of characterizing the sample source(s). Three groups of minerals are recognized: I) aluminian-chromian pyroxene, pyrope garnet and chromian spinel, which represent disaggregated fragments of spinel, spinel+garnet and garnet facies peridotite; II) low-Cr aluminian pyroxene that occurs as megacrysts are high pressure phases (7-12 kb) being crystallized from an alkaline-like evolving magma; III) low-Cr aluminian diopside of crustal origin. Evidence of carbonatitic cryptic metasomatic enrichment is shown by clinopyroxenes of Groups I and II. The data do not support a kimberlitic affinity as it has been suggested for the diatremes. Rather, they are interpreted as vents related to the alkaline magmatism affecting the area in Late Cretaceous. The alkaline parental magma of the pyroxene megacrysts was generated from a metasomatized mantle at garnet facies that incorporated fragments of the surrounding still fertile mantle. Presumably at spinel-facies level the magma began to fractionate the megacrysts, whose crystallization proceeded over a large range of falling pressure and temperature. The chemical similarities between Group III clinopyroxenes and those from the differentiated lithotypes indicate that the magma carried this mineral phase on its evolution, at crustal conditions, towards a more evolved alkaline composition. Still, a non-cognate origin for the Group III clinopyroxenes cannot be discarded.